Fuel tube and manufacturing method thereof

A laminated fuel tube with an aromatic polyamide resin inner layer and aliphatic polyamide resin outer layer, bonded with a specific fatty acid amide compound, addresses durability and adhesion issues, ensuring low fuel permeability, flexibility, and cost-effectiveness.

JP7602882B2Active Publication Date: 2024-12-19SUMITOMO RIKO CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2020149524
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-09-07
Publication Date
2024-12-19
Estimated Expiration
2040-09-07

AI Technical Summary

Technical Problem

Conventional fuel tubes made of aromatic polyamide resin like PA9T exhibit poor durability, flexibility, and adhesion issues, leading to increased complexity and cost due to the need for adhesive layers and potential interlayer gaps.

Method used

A laminated fuel tube design using an aromatic polyamide resin inner layer and an aliphatic polyamide resin outer layer, bonded with a specific fatty acid amide compound, eliminating the need for adhesive layers and enhancing interlayer adhesion through melt extrusion molding.

Benefits of technology

The fuel tube achieves high interlayer adhesion, low fuel permeability, flexibility, and resistance to low-temperature impacts while maintaining a lightweight and cost-effective structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602882000004
    Figure 0007602882000004
  • Figure 0007602882000001
    Figure 0007602882000001
  • Figure 0007602882000002
    Figure 0007602882000002
Patent Text Reader

Abstract

To provide a tube for a fuel which is excellent in fuel low permeability and also excellent in interlayer adhesion, and a production method of the same.SOLUTION: A tube for a fuel includes a tubular inner layer 1 made of a composition containing an aromatic polyamide resin as a main component, and an outer layer 2 that is provided in contact with its outer peripheral surface and is made of a composition containing an aliphatic polyamide resin as a main component, in which the inner layer contains an aliphatic amide compound obtained by dehydration condensation of the following components (A) and (B), and the inner layer and the outer layer are interlayer-bonded. (A) Saturated aliphatic monocarboxylic acid having 18 to 50 carbon atoms. (B) Diamine having 2 to 21 carbon atoms.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to fuels for automobiles, etc. (gasoline, alcohol-blended gasoline, diesel fuel, etc.) The present invention relates to a fuel tube used for transporting fuel, etc., and a method for manufacturing the same. [Background technology]

[0002] In recent years, regulations on fuel gas evaporation from automobiles have become stricter. Various types of low permeability fuel tubes are being considered. Previously, tubes were made of fluororesin, but now, more stringent fuel permeability requirements are required. However, the thickness of the fluororesin layer must be made thick, which makes the hose expensive. Therefore, resins that are cheaper than fluororesins and have excellent low fuel permeability are available, such as Aromatic resins such as polyphenylene sulfide resin (PPS) and polyamide 9T (PA9T) Polyamide resins, aromatic polyester resins such as polybutylene terephthalate (PBT) Tubes with a low fuel permeability layer made of these resins have been offered in various forms in recent years. It has been proposed (see, for example, Patent Documents 1 to 4). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 10-138372 [Patent Document 2] JP2003-287165A [Patent Document 3] JP2003-110736A [Patent Document 4] JP 2011-214592 A Summary of the Invention [Problem to be solved by the invention]

[0004] By the way, aromatic polyolefins such as PA9T, which are used as tube materials and have particularly excellent low fuel permeability, Polyamide resin has high rigidity, and if it is used alone to make a single-layer tube, it will be flexible. It has poor mechanical properties, is particularly vulnerable to shock at low temperatures, and is prone to tube cracking. In order to achieve this, the thickness of the aromatic polyamide resin layer is reduced, and the outer periphery of the aromatic polyamide resin layer is coated with an aliphatic polyamide resin. A laminated tube with an outer layer made of a thermoplastic resin with excellent flexibility, such as polyethylene resin. However, aromatic polyamide resins have poor adhesion to other materials. Therefore, when laminating the inner layer and the outer layer, an adhesive layer is usually provided at the interface between the two layers. Therefore, the manufacturing process becomes complicated due to the adhesive layer, and the tube weight increases. In addition, the composition of the inner layer may contain small molecules for adhesion. When fatty acid salts of the above are used, the cleavage reaction of the amide bond in the polyamide resin proceeds, resulting in a decrease in the strength of the resin. This can lead to problems such as:

[0005] The present invention has been made in consideration of the above circumstances, and provides a fuel-resistant composite material having excellent low fuel permeability and interlayer structure. The object of the present invention is to provide a fuel tube having excellent adhesive properties and a method for manufacturing the same. [Means for solving the problem]

[0006] In order to achieve the above object, the present invention provides a composition containing an aromatic polyamide resin as a main component. A tubular inner layer consisting of a tubular inner layer and a ... and an outer layer made of a composition which contains the following components (A) and (B) by dehydration and shrinkage: The inner layer and the outer layer are bonded to each other. The first gist of the present invention is a fuel tube characterized by the above. (A) Saturated aliphatic monocarboxylic acid having 18 to 50 carbon atoms (B) Diamines with 2 to 21 carbon atoms

[0007] The present invention also provides a tubular tube having an inner layer made of a composition containing an aromatic polyamide resin as a main component, an outer layer made of a composition containing an aliphatic polyamide resin as a main component and provided in contact with the outer peripheral surface of the outer layer; and the inner layer is made of the above-mentioned (A) and (B) components, and the following (C) component is subjected to dehydration shrinkage. The inner layer and the outer layer are bonded to each other. The second gist of the present invention is a fuel tube characterized in that (C) Polybasic acids with 2 to 14 carbon atoms

[0008] Furthermore, the present invention relates to a tubular inner layer made of a composition mainly composed of an aromatic polyamide resin. An outer circumferential surface of the outer circumferential surface is provided with an outer circumferential surface made of a composition mainly composed of an aliphatic polyamide resin. and a layer, the inner layer containing a specific fatty acid amide compound, a fuel cell having an alicyclic structure, and the inner layer and the outer layer are bonded to each other by interlayer bonding. The third point is the tube.

[0009] The present invention also provides a method for producing the fuel tube according to the first to third aspects, comprising the steps of: A composition mainly composed of an aromatic polyamide resin for forming the outer layer and an aliphatic polyamide resin for forming the outer layer. The composition mainly composed of a fluororesin is co-extruded by melt extrusion molding to produce a fuel tube. The fourth point is the law.

[0010] That is, the present inventors have conducted extensive research to solve the above problems. An aromatic polyamide resin such as PA9T with excellent permeability is used as the inner layer, and an aliphatic polyamide resin such as PA12 is used as the outer layer. Regarding a laminated tube having an outer layer made of polyamide resin, interlayer adhesion between the inner layer and the outer layer In the course of this research, we have focused on improving the properties of the laminated tube. ,Poor interlayer adhesion between the inner layer and the outer layer is, Linear expansion coefficient of the aliphatic polyamide resin used as the outer layer material and the aromatic polyamide resin used as the inner layer material Due to the difference in the number of holes, even if the material is bonded when it is melted, tiny physical gaps may occur after cooling. The inventors of the present invention have found that one of the reasons for this is that the inner layer material By blending a specific fatty acid amide compound into the inner layer material, It bleeds out onto the surface of the aromatic polyamide resin used as the raw material, and certain fatty acid amide compounds The saturated aliphatic part of the outer layer is bonded to the aliphatic polyamide resin by hydrogen bonding, The amide bond of a certain fatty acid amide compound is bonded to the aromatic polyamide resin, which is the inner layer material, and water. This is because bonding by elementary bonds suppresses the occurrence of minute physical voids after cooling. It was found that the desired interlayer adhesive strength can be obtained by this method, and the present invention was completed. Effect of the Invention

[0011] As described above, the fuel tube of the present invention is mainly composed of an aromatic polyamide resin such as PA9T. A tubular inner layer made of a resin composition mainly composed of an aliphatic polyamide resin. and an outer layer made of a material, and the resin composition for forming the inner layer contains a specific fatty acid amide compound. Therefore, the fuel hose of the present invention has high interlayer adhesion and is lightweight. It has excellent low fuel permeability, flexibility, low temperature impact resistance, and heat resistance. In the fuel tube of the present invention, the layers can be bonded without adhesive. In addition, because the material costs are low, the device can be manufactured at low cost despite its high performance as described above. It is possible to achieve this.

[0012] Furthermore, when an innermost layer made of a fluorine-based resin is further provided on the inner peripheral surface of the inner layer, It has excellent low fuel permeability.

[0013] The fuel tube is made of a resin composition for forming an inner layer and a resin composition for forming an outer layer. By co-extrusion of the inner layer material with the above-mentioned polyamide, a specific fatty acid amide group is obtained. The action of the mixture allows interlayer bonding without the use of adhesives. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a diagram showing a configuration of an example of a fuel tube of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Next, an embodiment of the present invention will be described.

[0016] The fuel hose of the present invention, for example as shown in FIG. 1, comprises a tubular inner layer 1 for passing fuel. An outer layer 2 is formed and laminated on the outer peripheral surface of the core. The inner layer 1 is made of a tubular composition mainly composed of an aromatic polyamide resin, and the outer periphery an outer layer 2 made of a composition mainly composed of an aliphatic polyamide resin provided in contact with the surface; The inner layer 1 is made of a fatty acid amine obtained by dehydrating and condensing the following components (A) and (B): The adhesive layer contains an oxide compound, and the inner layer and the outer layer are bonded to each other. The "main component" of the aromatic polyamide resin and the aliphatic polyamide resin is the resin. It is a substance that has a large effect on the properties of the entire fat composition. It means 50% by weight or more. (A) Saturated aliphatic monocarboxylic acid having 18 to 50 carbon atoms (B) Diamines with 2 to 21 carbon atoms

[0017] The inner layer 1 is made of a tubular composition mainly composed of an aromatic polyamide resin, and the outer periphery an outer layer 2 made of a composition mainly composed of an aliphatic polyamide resin provided in contact with the surface; The inner layer 1 is made of a material obtained by dehydrating and condensing the following component (C) in addition to the components (A) and (B): The inner layer and the outer layer are interlayer-bonded to each other. The structure is as follows. (C) Polybasic acids with 2 to 14 carbon atoms

[0018] Further, the tubular inner layer 1 is made of a composition mainly composed of an aromatic polyamide resin, and the outer an outer layer 2 provided in contact with the peripheral surface and made of a composition containing an aliphatic polyamide resin as a main component; The inner layer 1 contains a specific fatty acid amide compound, and the fatty acid amide compound It has an alicyclic structure, and has a structure in which the inner layer 1 and the outer layer 2 are bonded to each other.

[0019] Examples of the aromatic polyamide resin used as the material for forming the inner layer 1 include polyamide. Amide 4T (PA4T), Polyamide 6T (PA6T), Polyamide MXD6 (PAMX D6), Polyamide 9T (PA9T), Polyamide 10T (PA10T), Polyamide 1 1T (PA11T), Polyamide 12T (PA12T), Polyamide 13T (PA13T These may be used alone or in combination of two or more. From the viewpoints of adhesiveness and barrier properties, PA9T is preferably used.

[0020] As described above, the material for the inner layer 1 is a saturated aliphatic monocarboxylic acid having 18 to 50 carbon atoms. Contains fatty acid amide compounds obtained by dehydration condensation of acids and diamines with 2 to 21 carbon atoms The saturated aliphatic monocarboxylic acid having 18 to 50 carbon atoms is preferably a monocarboxylic acid having 18 to 50 carbon atoms. The saturated aliphatic monocarboxylic acid is a dicarboxylic acid having a molecular weight of 100 to 300. If the number of carbon atoms in the amine is less than the above range, the hydrogen bond with the aliphatic polyamide resin may be weak. On the other hand, if the number of carbon atoms exceeds the above range, bleeding out of the aromatic polyamide occurs. Specific examples of the above-mentioned saturated aliphatic monocarboxylic acid include Examples of such acids include stearic acid, tricosyl acid, lignoceric acid, pentacosyl acid, nervosyl acid, and glyceryl acid. carboxylic acid, cerotic acid, montanic acid, melissic acid, and other commercially available straight chain fatty acids with 18 to 50 carbon atoms. Unsubstituted saturated aliphatic monocarboxylates, such as compounds with a primary carboxyl group on a chain alkyl group. These may be used alone or in combination of two or more. Among the aliphatic monocarboxylic acids, Montana is the most popular because of its excellent hydrogen bonding with aliphatic polyamides. Of these, phosphate is preferably used. The diamine having 2 to 21 carbon atoms is preferably a diamine having 2 to 10 carbon atoms. In other words, if the carbon numbers of the saturated aliphatic monocarboxylic acid and the diamine are less than the above range, the aromatic polyamine will not be easily reacted with the aromatic polyamine. This is because the hydrogen bond with the triamide resin becomes weak. Conversely, if the number of carbon atoms exceeds the above range, This is because the compatibility with the aromatic polyamide resin decreases. Examples of the diamines include ethylenediamine, 1,3-propanediamine, and 1,4-butanediamine. , hexamethylenediamine, metaxylenediamine, tolylenediamine, paraxylene Diamine, phenylenediamine, isophoronediamine, 1,10-decanediamine, 1,1 2-Dodecanediamine, 1,2-Cyclohexanediamine, 1,3-Cyclohexanediamine cyclohexanediamine, 1,4-cyclohexanediamine, 1,3-bisaminomethylcyclohexane, 1,4 -Bisaminomethylcyclohexane, 3-aminomethyl-3,5,5-trimethylcyclohexane Hexylamine, bicyclo[2.2.1]heptane-2,3-diyldimethanamine, 4,4 -Diaminodicyclohexylmethane, 4,4'-methylenebis(2-methylcyclohexyl) 2,2'-dimethyl-4,4'-methylenebis(cyclohexylamine), Among them, alicyclic diamines are more preferable. As the alicyclic diamine, 1,2-Cyclohexanediamine, 1,3-Cyclohexanediamine, 1,4-Cyclohexane Sandiamine, 1,3-bisaminomethylcyclohexane, 1,4-bisaminomethylcyclohexane Cyclohexane, 3-aminomethyl-3,5,5-trimethylcyclohexylamine, Bis(cyclohexyl)amine 2.2.1]heptane-2,3-diyldimethanamine, 4,4-diaminodicyclohexyl Silmethane, 4,4'-methylenebis(2-methylcyclohexylamine), 2,2'- Dimethyl-4,4'-methylenebis(cyclohexan-1-ylamine) is an example. These may be used alone or in combination of two or more. Among the above diamines, aromatic polyamines are preferred. 1,3-bisaminomethylcyclohexane is preferred because of its excellent hydrogen bonding with diamide. It is often used.

[0021] Furthermore, as described above, the material for the inner layer 1 is preferably a saturated aliphatic monocarbonate having 18 to 50 carbon atoms. In addition to the diamine components with carbon numbers of 2 to 21, polybasic acids with carbon numbers of 2 to 14 are dehydrated and condensed. The fatty acid amide compound obtained by the above reaction is preferably a polybasic fatty acid having 2 to 10 carbon atoms. That is, if the number of carbon atoms in the polybasic acid is less than the above range, the aliphatic polyamide resin On the other hand, if the number of carbon atoms exceeds the above range, the hydrogen bond with the aromatic polyamide becomes weak. This is because excessive bleeding out from the mid is caused. Examples include oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, Azelaic acid, Sebacic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid Examples of aromatic dicarboxylic acids include phthalic acid and terephthalic acid. Among them, alicyclic dicarboxylic acids are more preferable. Alicyclic dicarboxylic acids include 1,1-cyclopropanedicarboxylic acid, 1,2-cyclopropanedicarboxylic acid, Panedicarboxylic acid, 1,1-cyclobutanedicarboxylic acid, 1,2-cyclobutanedicarbo Acid, 1,3-cyclobutanedicarboxylic acid, 3,4-diphenyl-1,2-cyclobutane Dicarboxylic acid, 2,4-diphenyl-1,3-cyclobutanedicarboxylic acid, 3,4-bis (2-Hydroxyphenyl)-1,2-cyclobutanedicarboxylic acid, 2,4-bis(2- Hydroxyphenyl)-1,3-cyclobutanedicarboxylic acid, 1-cyclobutene-1,2 -dicarboxylic acid, 1-cyclobutene-3,4-dicarboxylic acid, 1,1-cyclopentane dicarboxylic acid Carboxylic acid, 1,2-cyclopentanedicarboxylic acid, 1,3-cyclopentanedicarboxylic acid Acid, 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1, 4-Cyclohexanedicarboxylic acid, 1-cyclohexene-1,2-dicarboxylic acid, 4-cyclohexanedicarboxylic acid Cyclohexene-1,2-dicarboxylic acid, 1,4-(2-norbornene)dicarboxylic acid, 2 ,3-Norbornanedicarboxylic acid, 3-Methyl-4-cyclohexene-1,2-dicarboxylic acid carboxylic acid, 4-methyl-4-cyclohexene-1,2-dicarboxylic acid, spiro[3.3]heptane Tan-2,6-dicarboxylic acid, 1,1-cyclohexanediacetic acid, 1,4-cyclohexane Diacetic acid, cis-1,2,2-trimethyl-1,3-cyclopentanedicarboxylic acid, Cyclo[2.2.2]octane-1,4-dicarboxylic acid, bicyclo[2.2.2]octane -2,3-dicarboxylic acid, 2,5-dioxo-1,4-bicyclo[2.2.2]octane Dicarboxylic acid, 1,3-adamantanedicarboxylic acid, 4,8-dioxo-1,3-adamantane 2,6-Decalindicarboxylic acid, 1,5-Decalindicarboxylic acid, 1,6-Decalindicarboxylic acid, 2,3-Decalindicarboxylic acid, 2,7-Decalindicarboxylic acid These may be used alone or in combination of two or more. Among the above polybasic acids, those having excellent adhesion to aliphatic polyamide resins are used in combination. From this viewpoint, 1,1-cyclohexanediacetic acid is preferably used.

[0022] The above-mentioned fat in the composition mainly composed of an aromatic polyamide resin which is the material for the inner layer 1 The content of the acid amide compound is preferably in the range of 0.05 to 5% by weight, more preferably The range is preferably 0.1 to 1% by weight. In other words, if the content is less than the above range, the fatty acid alkanes may become This is because the desired interlayer adhesion effect due to the imido compound cannot be obtained. In this case, the desired interlayer adhesion effect is not achieved due to excessive uneven distribution in the vicinity of the adhesive interface. Because you won't be able to get it.

[0023] Examples of the aliphatic polyamide resin used as the material for forming the outer layer 2 include polyamide. Polyamide 46 (PA46), Polyamide 6 (PA6), Polyamide 66 (PA66), Poly Polyamide 99 (PA99), Polyamide 610 (PA610), Polyamide 612 (PA6 12), Polyamide 11 (PA11), Polyamide 912 (PA912), Polyamide 1 2 (PA12), copolymer of polyamide 6 and polyamide 66 (PA6 / 66), polyamide Examples of such copolymers include polyamide 6 and polyamide 12 (PA6 / 12). Or two or more types may be used in combination.

[0024] The materials for the inner layer 1 and the outer layer 2 include resins as their main components and additives thereto. In addition to the specific fatty acid amide compounds, carbon black, titanium oxide, etc. may also be used as necessary. Pigments, calcium carbonate and other fillers, fatty acid esters, mineral oil, butylbenzene Plasticizers such as sulfonamides, hindered phenol-based antioxidants, phosphorus-based heat stabilizers, and other acids Antioxidants, heat aging inhibitors, impact resistance agents such as α-polyolefin, UV inhibitors, antistatic agents Contains reinforcements such as organic fibers, glass fibers, carbon fibers, and metal whiskers, as well as flame retardants. It is also acceptable.

[0025] The fuel hose of the present invention shown in FIG. 1 can be produced, for example, as follows. That is, the material for the inner layer 1 and the material for the outer layer 2 are prepared as described above. The materials for forming each layer are then extruded, for example, using an extrusion molding machine (a multi-layer extrusion machine manufactured by Plastics Engineering Research Institute Co., Ltd.). The inner layer material is melt-kneaded at 260 to 330°C, and the outer layer material is melt-kneaded at 200 to 250°C. The mixture was co-extruded while being kneaded at 50°C, and the co-extruded molten tube was passed through a sizing die. The fuel hose has a two-layer structure in which an outer layer 2 is formed on the outer peripheral surface of an inner layer 1 by passing the fuel hose through a wire. By this melt extrusion (co-extrusion) molding, the inner layer 1 can be produced. The specific fatty acid amide compound in the material ensures good adhesion between the two layers. become.

[0026] In addition, when the hose is formed into a bellows shape, the co-extruded molten tube is corrugated. By passing the material through a molding machine, a bellows-shaped hose of predetermined dimensions can be produced.

[0027] In the fuel hose of the present invention thus obtained, the inner diameter of the hose is 1 to 40 mm. The outer diameter of the hose is preferably within the range of 2 to 36 mm, and more preferably within the range of 2 to 44 The thickness of the inner layer 1 is preferably within a range of 3 to 40 mm, and more preferably within a range of 3 to 40 mm. The thickness is preferably within a range of 0.02 to 1.0 mm, and particularly preferably 0.05 to 0.6 mm. The thickness of the outer layer 2 is preferably within a range of 0.03 to 1.5 mm, and particularly preferably within a range of 0.03 to 1.5 mm. Or it is in the range of 0.05 to 1.0 mm.

[0028] The fuel hose of the present invention is not limited to the two-layer structure shown in FIG. For example, it is also possible to form a three-layer structure in which an innermost layer is formed on the inner peripheral surface of the inner layer 1. do.

[0029] If the innermost layer is made of a fluorine-based resin, the fuel hose of the present invention The fluororesin is preferably a fluororesin having a higher fuel permeability. , Polyvinyl fluoride (PVF), Polyvinylidene fluoride (PVDF), Poly Chlorotrifluoroethylene (CTFE), Polytetrafluoroethylene (PTFE), Tetrafluoroethylene-hexafluorocopolymer (FEP), tetrafluoroethylene Perfluoroalkyl vinyl ether copolymer (PFA), tetrafluoroethylene Hexafluoropropylene vinylidene fluoride copolymer (THV), ethylene and tere Copolymer of ethylene and polychlorotrifluoroethylene (ETFE) Copolymers of polyethylene (ECTFE), their modified copolymers, various graft copolymers, Aggregates and blends, and further, carbon black, carbon fiber, carbon nanotubes, etc. Examples of the conductive material include conductive fluorine-based resins that have been given conductivity by adding conductive polymers or the like. These may be used alone or in combination of two or more.

[0030] The fuel hose of the present invention, in which an innermost layer is formed on the inner peripheral surface of the inner layer 1, can be, for example, That is, the above-mentioned material for the inner layer 1 and the material for the outer layer 2 can be prepared as follows. In both cases, the material for the innermost layer is prepared, and the innermost layer is made of the inner layer 1 and the outer layer 2 according to the manufacturing method described above. Alternatively, a separate innermost layer extruder is used to extrude the innermost layer. The innermost layer is extruded on the inner peripheral surface of the inner layer 1 formed by the manufacturing method, and the molten chuck obtained by this is By passing the tube through a sizing die, the innermost layer is formed on the inner peripheral surface of the inner layer 1. A fuel hose can be made.

[0031] In the fuel hose of the present invention, the thickness of the innermost layer is within a range of 0.03 to 0.5 mm. The thickness of the innermost layer is preferably in the range of 0.05 to 0.3 mm, and more preferably in the range of 0.05 to 0.3 mm. In the fuel hose of the present invention, the thickness of the inner layer 1 and the outer layer 2, the inner diameter of the hose, and the outer diameter thereof are preferably The suitable range is as described above.

[0032] In addition, the fuel hose of the present invention may be provided with a suitable material, for example, on the outer periphery of the outer layer 2, as required. It is also acceptable to have a structure in which an outermost layer made of

[0033] The fuel hose of the present invention is capable of handling gasoline, alcohol-blended gasoline, diesel fuel, CN It is well suited as a hose for transporting automobile fuels such as compressed natural gas (NG) and liquefied petroleum gas (LPG). Suitable examples of the gas that can be used include, but are not limited to, methanol, hydrogen, dimethyl ether, etc. It can also be used as a fuel transport hose for fuel cell vehicles, such as DME. EXAMPLES

[0034] Next, examples will be described together with comparative examples. However, the present invention is not limited to these examples. It is not something that can be determined.

[0035] First, prior to the Examples and Comparative Examples, the materials shown below were prepared.

[0036] [PA9T] Genestar N1001A (melting point: 304℃), manufactured by Kuraray

[0037] [PA6T] Arlen AE4200, manufactured by Mitsui Chemicals

[0038] [MXD6] Reny S6007, manufactured by Mitsubishi Gas Chemical Company

[0039] [Fatty acid amide compound (i)] Slipax E (ethylene bisstearic acid amide, a saturated aliphatic monocarbonate with 18 carbon atoms) carboxylic acid / diamine with 2 carbon atoms), manufactured by Mitsubishi Chemical Corporation

[0040] [Fatty acid amide compound (ii)] Slipax ZHB (Hexamethylenebisbehenamide, a saturated fatty acid moiety with 22 carbon atoms) (aminocarboxylic acid / diamine with 6 carbon atoms), manufactured by Mitsubishi Chemical Corporation

[0041] [Fatty acid amide compound (iii)] In a reactor equipped with an agitator, a thermometer, and a water divider, montanic acid (Wako 850 parts by mass of maleic acid (manufactured by Wako Pure Chemical Industries, Ltd.) as a dicarboxylic acid, and 2 parts by mass of maleic acid (manufactured by Wako Pure Chemical Industries, Ltd.) as a dicarboxylic acid. 00 parts by mass, and 300 parts by mass of hexamethylenediamine (manufactured by Wako Pure Chemical Industries, Ltd.) as a diamine The mixture was added to the flask and subjected to a condensation reaction while dehydrating under a nitrogen atmosphere at 180 to 220°C for 3 to 5 hours. The mixture was cooled to room temperature to obtain fatty acid amide compound (iii).

[0042] [Fatty acid amide compound (iv)] In a reactor equipped with an agitator, a thermometer, and a water divider, montanic acid was added as an aliphatic monocarboxylic acid. (manufactured by Wako Pure Chemical Industries, Ltd.) 850 parts by mass and 1,1-cyclohexyl 1,2-dihydropyridine as an alicyclic dicarboxylic acid 200 parts by mass of 1,3-bis(aminoethyl)-2,4-dimethylaminopropyl diamine (manufactured by Wako Pure Chemical Industries, Ltd.) 300 parts by mass of 2-methylcyclohexane (manufactured by Wako Pure Chemical Industries, Ltd.) was added, and the mixture was stirred for 18 hours under a nitrogen atmosphere. The mixture is subjected to a condensation reaction while dehydrating at 0 to 220°C for 3 to 5 hours, and then cooled to room temperature. As a result, fatty acid amide compound (iv) was obtained.

[0043] [Saturated Aliphatic Metal Salts] Zinc stearate, manufactured by Wako Pure Chemical Industries, Ltd.

[0044] [PA12] Rilsan AESN NOIR P20TL, manufactured by Arkema

[0045] [Impact resistance agent] TAFMER A-4085 (α-polyolefin), manufactured by Mitsui Chemicals

[0046] [Plasticizer] Butylbenzenesulfonamide, manufactured by Wako Pure Chemical Industries, Ltd.

[0047] [Heat-resistant anti-aging agent] Irganox 1010, manufactured by Ciba Japan

[0048] [Fluororesin] Neoflon RP5000, manufactured by Daikin Industries, Ltd.

[0049] Next, a hose was produced using the above materials as described below.

[0050] [Examples 1 to 10, Comparative Examples 1 to 2] The innermost layer material (Examples 9 and 10 only), the inner layer material, and the outer layer material shown in Tables 1 to 3 below. The materials were prepared and then mixed in an extrusion machine (a multi-layer extrusion machine manufactured by the Plastics Engineering Research Institute). The mixture was melt-kneaded using the above ingredients and co-extruded to produce a smooth hose with an inner diameter of 6 mm. In addition, if the smooth hose manufactured above has a two-layer structure, the thickness of the inner layer is 0.3 mm and the thickness of the outer layer is 0 7mm, and in the case of a three-layer structure, the thickness of the innermost layer is 0.05mm / thickness of the inner layer is 0.25mm / The thickness of the outer layer was 0.7 mm.

[0051] Using the hoses of the examples and comparative examples thus obtained, each characteristic was evaluated according to the following criteria. Sexuality was evaluated.

[0052] [Fuel permeation amount] For each hose, a pressure-equalizing hose permeability measuring device (GTR-TUBE, manufactured by GTR Tech Co., Ltd.) 3-TG) was used, and toluene / isooctane / ethanol was mixed at 45:45:10 (volume ratio). The permeability coefficient of simulated alcohol-added gasoline mixed in the ratio of 1:1 was measured at 40°C for one month. (Unit: mg / m / day) The values ​​shown in the table are those at equilibrium. If this value is less than 50 (mg / m / day), it is marked as ○, and if it is less than 50 (mg / m / day), it is marked as ○. y) or above was rated as ×.

[0053] [Interlayer adhesion strength] Each hose was cut into a strip of 10 mm width to prepare a sample. Between the layers of the film (between the inner layer and the outer layer in Examples 1 to 10 and Comparative Examples 1 and 2; between the inner layer and the outer layer in Examples 15 to 20) In this test, the innermost layer / inner layer and the inner layer / outer layer were peeled off, and the test pieces were subjected to the same test using the tensile tester. The 180° peel strength (N / cm) was measured at a tensile speed of 50 mm / min. In addition, the target value for good interlayer adhesion is set as 25 N / cm or more for the peel strength. The evaluation is indicated as ○, 20N / cm or more but less than 25N / cm is indicated as △, and 20N In the present invention, evaluations of △ or higher (○, △) were is required.

[0054] [Table 1]

[0055] [Table 2]

[0056] [Table 3]

[0057] From the above results, it can be seen that the example products all have small fuel permeation rates and excellent interlayer adhesion. It can be seen that.

[0058] In contrast, the Comparative Example 1 product is a laminate of a PA9T inner layer and a PA12 outer layer, just like the Example product. However, the inner layer material does not contain a specific fatty acid amide compound, unlike the example product. In the case of Comparative Example 2, the inner layer was foamed and could not be molded. I did. [Industrial Applicability]

[0059] The fuel hose of the present invention is capable of handling gasoline, alcohol-blended gasoline, diesel fuel, CN Suitable as a hose for transporting automobile fuels such as compressed natural gas (G), LPG (liquefied petroleum gas), etc. can be used. [Explanation of symbols]

[0060] 1 Inner layer 2 outer layer

Claims

1. A fuel tube comprising: a tubular inner layer made of a composition mainly composed of an aromatic polyamide resin; and an outer layer provided in contact with the outer peripheral surface of the inner layer and made of a composition mainly composed of an aliphatic polyamide resin, wherein the inner layer contains a fatty acid amide compound obtained by dehydration condensation of the following components (A), (B) and (C), the content of the fatty acid amide compound in the composition mainly composed of the aromatic polyamide resin is in the range of 0.05 to 5% by weight, and the inner layer and the outer layer are interlaminarly bonded. (A) Saturated aliphatic monocarboxylic acid having 18 to 50 carbon atoms (B) Diamine having 2 to 21 carbon atoms (C) Polybasic acid having 2 to 14 carbon atoms

2. A fuel tube comprising: a tubular inner layer made of a composition mainly composed of an aromatic polyamide resin; and an outer layer provided in contact with the outer peripheral surface of the inner layer and made of a composition mainly composed of an aliphatic polyamide resin, the inner layer being obtained by dehydration condensation of the following components (A) and (B) and containing a fatty acid amide compound having an alicyclic structure, the content of the fatty acid amide compound in the composition mainly composed of the aromatic polyamide resin being in the range of 0.05 to 5% by weight, and the inner layer and the outer layer being interlaminarly bonded. (A) Saturated aliphatic monocarboxylic acid having 18 to 50 carbon atoms (B) Diamine having 2 to 21 carbon atoms

3. 3. The fuel tube according to claim 2, wherein the fatty acid amide compound is a fatty acid amide compound obtained by dehydration condensation of the following component (C) in addition to the components (A) and (B): (C) Polybasic acid having 2 to 14 carbon atoms

4. 4. The fuel tube according to claim 1, wherein the aromatic polyamide resin composition is mainly composed of polyamide 9T (PA9T).

5. 5. The fuel tube according to claim 1, further comprising an innermost layer made of a fluorine-based resin on an inner peripheral surface of the inner layer.

6. 6. A method for producing the fuel tube according to claim 1, comprising co-extruding a composition containing an aromatic polyamide resin as a main component for forming the inner layer and a composition containing an aliphatic polyamide resin as a main component for forming the outer layer by melt extrusion molding.

Citation Information

Patent Citations

  • Multilayer fuel tube

    JP1998138372A

  • Heat-shrinkable film

    JP2001310386A

  • Method for manufacture of polyamide resin composition and molded product obtained therefrom

    JP2002292625A

  • Moving image distribution server

    JP2003110736A

  • Fuel hose

    JP2003287165A